2022
DOI: 10.1111/evj.13861
|View full text |Cite
|
Sign up to set email alerts
|

Hoof morphometry in a population of lame and nonlame working donkeys in Pakistan

Abstract: Background: Hoof morphometry, conformation and shoeing practices have all been associated with lameness in horses. Hoof morphometry in working donkeys in Pakistan has not been objectively measured.Objectives: To quantitatively assess hoof morphology in donkeys, to identify factors underlying hoof morphology, and interrelationships between conformation, lameness, and shoeing status.Study design: Cross-sectional study.Methods: Donkeys were assessed in-harness using a modified five-point lameness scale by two vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The majority of donkey owners reported lameness in their donkeys. Only seven owners did not report lameness at any time, which is consistent with a recent study in this population [26]. While not common, owners in the current study also reported their donkeys becoming lame due to traumatic events, such as slipping, being hit by a vehicle, or overloading.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The majority of donkey owners reported lameness in their donkeys. Only seven owners did not report lameness at any time, which is consistent with a recent study in this population [26]. While not common, owners in the current study also reported their donkeys becoming lame due to traumatic events, such as slipping, being hit by a vehicle, or overloading.…”
Section: Discussionsupporting
confidence: 90%
“…While the impact of the growth of the dairy sector and farriers servicing both sectors were not specifically investigated in the current study, the overlap does create some concerns for the working equid industry. Firstly, the characteristics of a functional working donkey hoof and that of a dairy animal differ markedly [26,27]. A lack of understanding of the similarity or differences in hoof characteristics of these species could be detrimental to welfare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The welfare standards of working equids remain inadequate in LMICs (13,15). Eye infections, infectious diseases, colic, skin diseases, poor physical condition, respiratory infections, back pain, injuries, exhaustion, wounds, malnutrition, famine, fracture, heat stress, dehydration (2, 10), trauma, insect exposure (16), sprains, lameness, as well as other catastrophic injuries (15,17) are some of the most common welfare issues (Figure 2). They are prone to locomotor system diseases (18), which become even more common when subjected to hazardous working situations (19).…”
Section: Introductionmentioning
confidence: 99%